Effect of esketamine-based patient-controlled intravenous analgesia on postoperative pain and quality of recovery after video-assisted thoracoscopic lobectomy: A prospective, double-blind, randomized controlled trial - Ruirui Bi; Jiqiang Zhang; Ruijuan Liu; Lijuan Li; Yuxi Su; Mengjun Xu; Wenjun Yan (PLoS ONE, 2026)
Objective This double-blinded randomized study aimed to investigate the effects of esketamine-based patient-controlled intravenous analgesia (PCIA) on postoperative analgesia and quality of recovery in patients undergoing video-assisted thoracoscopic (VATS) lobectomy. Methods Patients undergoing selective VATS lobectomy were enrolled and randomly assigned (1:1) to receive PICA with 1.5 mg/kg esketamine (group K) or 1.5 mg/kg sufentanil (group S). Pain intensity was evaluated using the short-form of the McGill Pain Questionnaire (SF-MPQ) and the visual analog scale (VAS). The primary endpoint was the SF-MPQ score of patients on postoperative day 1. Results Between December 2021 and May 2022, 84 eligible patients received the allocated treatment, with 80 patients (40 per group) ultimately included in the analysis. The total SF-MPQ score in group K was lower than that in group S on postoperative day 1 ( P < 0.001) and day 2 ( P < 0.001). Additionally, the VAS-rest, VAS-movement and patients’ depression-related scores in group K were all significantly lower than those in group S on postoperative day 1 ( P = 0.012, P = 0.008 and P = 0.009, respectively) and day 2 (all P < 0.001), whereas the postoperative recovery quality was significantly higher in group K than that in group S on postoperative days 1 and 2 (both P < 0.001). A lower incidence of total adverse events (AEs) was observed in group K than in group S (15% vs. 35%, P = 0.039). Conclusion The use of 1.5 mg/kg esketamine in PCIA for postoperative analgesia in patients undergoing VATS lobectomy showed a promising analgesic effect and improved perioperative depression and postoperative recovery quality, with no severe AEs observed.